Kondisi mangrove di pesisir timur pulau Jemaja Kepuluan Anambas - Andrito, Wahyudi; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Universitas Riau, 2020)
Mangrove ecosystems are one of three important ecosystems in the coastal areas that supports global warming mitigation efforts. The existence of mangrove forests is needed to reduce the increased CO2 concentrations in the atmosphere. However, the rise of the water temperatures and sea levels indirectly affects the presence and condition of mangrove forests in coastal areas. The purpose of this study is to determine the condition of the mangrove community on the East Coast of Jemaja, Anambas Archipelagoes Regency. The survey method was used in this study and a series survey activities were conducted for a quadrant transect with a size of 10m by 10m in December 2019 - March 2020.The result shown that the five mangrove species were identified, such as Rhizophora apiculata, R. mucronata, Bruguiera gymnorrhiza, Ceriops tagal and Xylocarpus granatum. R. apiculata dominates with an important value index of 123.12%. While, the average density of mangroves and saplings in the study area was 3155 ± 785 individuals/ha and the average canopy cover was 84.03 ± 3.11%. With this finding, it can be concluded that the condition of mangroves in the East Coast of Jemaja is very dense and still in a good condition.